Relationship between spinal abnormalities and musculoskeletal pains in university students in Hamadan (Iran) - Sedigheh Sadate Mirbagheri; Saeedeh Sadate Mortazavi; Amir Rahmani Rasa; Jamshid Hossein Alizadeh (Vesnu Publications, 2013)
Introduction: The spine serves as the main support of the body. During activities, postural stability depends on the simultaneous function of the muscles, passive elements, and also the neural elements. The aim of this study was to investigate the relationship between spinal abnormalities and musculoskeletal pains in the areas related to these abnormalities in the students of Hamadan University of Medical Sciences. Materials and Methods: 241 students (157 females with the mean age of 19.42 years, SD=1.1 years; 84maleswith the mean age of 21.01 years, SD=2.25 years) voluntarily participated in this study. Spinal alignment was evaluated by posture screen, plumb line and the New York Test of the Lateral Head Deviation to determine the rates of forward head, shoulder asymmetry, kyphosis and lordosis. To determine the location and intensity of pain in the head, the left-and right-neck, the left- and right-shoulder and the low-back regions, a tailor-made questionnaire with visual analog scale was used. Finally, using the correlation coefficient, the data were statistically analyzed. Results: There was significant relationship between lateral head deviation and both headache and the left-side neck pain (P < 0.05). Kyphosis was significantly correlated with feeling pain in the right and the left shoulders and also with inters scapular pain (P < 0.05). Moreover, significant relationship between lordosis and low back pains was observed (P < 0.05). Conclusion: The results of this study indicate a signification relationship between the presence of some postural abnormalities and the incidence of musculoskeletal pain. Keywords: Spine, Shoulder, Forward head, Kyphosis abnormality, Lordosis abnormality, Musculoskeletal pains, Posture